Electric Aviation Development and Future Prospect - Li Zhoujinpeng (E3S Web of Conferences)
Electric vehicles have gained significant traction, with hybrid and fully electric cars and trucks increasingly replacing traditional fuel-powered vehicles. However, the development of electrified aircraft has received comparatively less public attention. This research study aims to explore the evolution of electric aviation and its future potential. It delves into the history of electric aviation and examines various types of electric propulsion systems, including all-electric, series hybrid, parallel hybrid, and turboelectric configurations. The study also analyzes the advantages and disadvantages of current electrified aircraft technologies. Additionally, it considers the policies and investments necessary to stimulate the advancement of electric aviation. As concerns over environmental issues and energy shortages grow, electrified aircraft could emerge as a viable alternative to gas turbine aircraft, offering reduced carbon emissions and lower operational costs. The purpose of this paper is to provide a comprehensive overview of the current state and future prospects of electric aviation, with a particular emphasis on its potential to revolutionize the aviation industry.